Impurity and gender in the Hebrew Bible - Goldstein, Elizabeth W. (Lexington Books, an imprint of The Rowman & Littlefield Publishing Group, Inc, 2015)
Narratives, genealogy, and gender in P -- Gender and impurity in P -- Expanding the notion of purity: gender, blood, and the Holiness code -- Blame it on a metaphor: female degradation and blood in Ezekiel -- Gender and impurity in Ezra-Nehemiah -- NDH as sin in the Scrolls -- Impurity in the foundation of Jews and Judaism